Assessment of Antioxidant Stability of Meat Pâté with Allium cepa Husk Extract - Irina Chernukha; Nadezhda Kupaeva; Daniil Khvostov; Yuliya Bogdanova; Jutta Smirnova; Elena Kotenkova (MDPI AG, 2023)
Antioxidants play a very important role in the food industry. Recently, both science and industry have shown substantial preference for natural antioxidants, including searching for antioxidant substances from natural sources without undesirable side effects. The purpose of this study was to evaluate the effect of adding Allium cepa husk extract at a volume of 68 or 34 <semantics>μ</semantics>L/g of unsalted blanched materials to replace 34% and 17% of the beef broth, respectively, which corresponded to a total antioxidant capacity (TAC) of 44.4 or 22.2 <semantics>μ</semantics>mol-equiv. Q/100 g meat pté (i.e., 13.42 or 6.71 mg of quercetin/100 g meat pté), on the quality and safety indicators of the developed meat pté. The TAC according to a ferric reducing antioxidant power assay, thiobarbituric acid reactive substances, and physicochemical and microbiological characteristics were determined during the storage of the meat pté. Proximal and UPLC-ESI-Q-TOF-MS analyses were also performed. The addition of yellow onion husk ethanolic extract to the meat pté at both volumes allowed the maintenance of an increased content of antioxidants, which contributed to a decrease in the generation of secondary products of lipid peroxidation for 14 days of storage at 4 <semantics>∘</semantics>C. The results of the microbiological analyses showed that the developed meat ptés were safe according to all indicators of microbial spoilage within 10 days of production. The results supported the use of yellow onion husk extract in the food industry to contribute to improving the functionality of meat products, developing products for a healthy lifestyle, and providing clean-label foods without or with a minimal content of synthetic additives.